A study of the self-perceived competencies regarding the knowledge and skills of healthcare providers in the Expanded Program on Immunization in Thailand: A mixed-methods study - Pregamol Rutchanagul; Wipada Sangnimitchaikul (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The Expanded Program on Immunization (EPI) has still been found to offer services that do not comply with standards. The purpose of this paper is to ascertain competency in terms of the knowledge and skills of the EPI staff. Design/methodology/approach - The research design was a mixed-methods approach. The quantitative method employed a questionnaire survey on the perceived competency of 382 EPI staffs from six regions in Thailand. This was paired alongside of the qualitative method, where four staffs were in-depth interviewed, and the performance of the EPI staffs was observed. Findings - The overall perceived competency in the work of immunization was at a high level. A comparative analysis between the quantitative and qualitative data showed findings in three categories. First, the perception of competency was high, and performance conformed to standards in the preparation of the setting and equipment for providing the service; second, the perception of competency was high, but in the performance of their work the participants did not comply completely with standards for scheduling the immunization appointments or for vaccine storage; and third, the perception of competency was either moderate or low, and the performance of work was inadequate for vaccine estimations, registering reports, and dealing with adverse events following immunization. Originality/value - The findings showed a gap between perception of knowledge-and-skill competency and actual practice in EPI service. Effective cooperation among involved organizations in order to improve the standard of performance in expanding the quality of EPI service provision in Thailand is suggested.